A history of the Arab peoples - Hourani, Albert Habib (New York, NY Warner Books, 1992)
Encyclopedic and panoramic in its scope, this fascinating work chronicles the rich, spiritual, political, and cultural institutions of Arab history through 13 centuries.
Preface -- Author's note -- Prologue -- Part I. The making of a world (seventh-tenth century). 1. A new power in an old world -- 2. The formation of an empire -- 3. The formation of a society -- 4. The articulation of Islam -- Part II. Arab Muslim societies (eleventh-fifteenth century). 5. The Arab Muslim world -- 6. The countryside -- 7. The life of cities -- 8. Cities and their rulers -- 9. Ways of Islam -- 10. The culture of the 'ulama -- 11. Divergent paths of thought -- 12. Culture of courts and peoples -- Part III. The Ottoman age (sixteenth-eighteenth century). 13. The Ottoman empire -- 14. Ottoman societies -- 15. The changing balance of power in the eighteenth century -- Part IV. The age of European empires (1800-1939). 16. European power and reforming governments -- 17. European empires and dominant elites -- 18. The culture of imperialism and reform -- 19. The climax of European power (1914-1939) -- 20. Changing ways of life and thought -- Part V. The age of nation-states (since 1939). 21. The end of the empires (1939-1962) -- 22. Changing societies (1940s and 1950s) -- 23. National culture (1940s and 1950s) -- 24. The climax of Arabism (1950s and 1960s) -- 25. Arab unity and disunity (since 1967) -- 26. A disturbance of spirits (since 1967) -- Maps -- Genealogies and dynasties -- Notes -- Bibliography -- Index of terms -- General index. Making of a world (seventh-tenth century) -- Arab Muslim societies (eleventh-fifteenth century) -- Ottoman age (sixteenth-eighteenth century) -- Age of European empires (1800-1939) -- Age of nation-states (since 1919).
Originally published: Cambridge, Mass. : Belknap Press of Harvard Uiversity Press, 1991.
Keywords: Arabs -- History; Arab countries -- History